Low-permeability polytetrafluoroethylene tube and preparation method thereof

Through presintering and thermal isostatic pressure treatment processes, the pores and defects caused by high melt viscosity and low flowability during the processing of polytetrafluoroethylene pipes are solved, and low permeability and high density of polytetrafluoroethylene pipes are achieved, which improves sealing performance and mechanical properties.

CN119735906APending Publication Date: 2025-04-01ZHENGZHOU HAITAIKE POLYMER TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510020394.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Due to its high melt viscosity and low flowability, polytetrafluoroethylene pipes are difficult to be evenly distributed during processing, resulting in pores and defects in the finished product, thereby improving permeability and affecting sealing performance and product life.

Method used

Presintering and hot isostatic pressure treatment processes are adopted to promote the initial crystallization of the material at a temperature of 200-300°C by presintering, gradually release internal stress, and further crystallize and close pores at a pressure of 60-80 MPa and a temperature of 330-400°C by thermal isostatic pressure treatment.

Benefits of technology

It significantly reduces the porosity of the material, improves the density and uniformity of the material, reduces the permeability, enhances the sealing and mechanical properties, especially in terms of excellent compression and bending resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735906A_ABST
    Figure CN119735906A_ABST
Patent Text Reader

Abstract

The invention discloses a low-permeability polytetrafluoroethylene tube and a preparation method thereof, and belongs to the technical field of polytetrafluoroethylene tubes. The preparation method of the low-permeability polytetrafluoroethylene tube comprises the following steps: respectively weighing the TFE / HFP copolymer, the assistant, the nucleating agent, the antioxidant and the antistatic agent in parts by weight for later use; uniformly mixing the TFE / HFP copolymer, the auxiliary agent, the nucleating agent, the antioxidant and the antistatic agent in a high-speed mixer; the mixture stored for a period of time is placed in a preforming machine to be pressed and formed, and a blank is prepared; the blank is placed on an extruder to be extruded, and a raw pipe blank is prepared; and drying and presintering the raw tube blank, and then carrying out hot isostatic pressing treatment on the raw tube blank to obtain the low-permeability polytetrafluoroethylene tube. The polytetrafluoroethylene tube prepared by the invention has excellent properties such as fatigue resistance, pressure resistance and bending strength, also has relatively low permeability, and can be applied to the field with strict requirements on permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polytetrafluoroethylene tubes, and in particular relates to a low-permeability polytetrafluoroethylene tube and a preparation method thereof. Background Art

[0002] Polytetrafluoroethylene (PTFE) is a high-performance material with excellent chemical stability, temperature resistance, corrosion resistance and low friction coefficient. It is widely used in various high-performance products, especially in the fields of wires and cables, fluid delivery pipelines, etc. However, due to its high melt viscosity and poor fluidity, it brings great difficulties to its processing, especially in applications that require high precision and high sealing, these problems are more prominent.

[0003] The melt viscosity of PTFE is much higher than that of general thermoplastics, which makes it difficult to flow and fill the mold during processing. Even at high temperatures, the melt of PTFE still shows a very high viscosity, making processing more difficult; due to the high melt viscosity, the fluidity of PTFE is also poor, resulting in the difficulty of uniform distribution of PTFE materials during extrusion, molding and other processing processes, which easily leads to pores and defects. Especially in the process of processing polytetrafluoroethylene dispersed resin paste extrusion pipes, due to the high viscosity and poor fluidity of PTFE melt, when the paste extrusion method is used to process the dispersed resin to prepare pipes, the melt is difficult to fully fill the tiny pores in the mold, resulting in more pores or microcracks inside the finished pipe. These pores or microcracks become channels for liquid or gas penetration, making the permeability of PTFE pipes high, which not only affects the sealing performance of the pipes, but may also cause leakage of liquid or gas, thereby affecting the service life and safety of the product, and cannot meet the needs of fields with strict permeability requirements.

[0004] Therefore, developing a polytetrafluoroethylene tube that can meet the above-mentioned strict requirements on permeability has become one of the problems that those skilled in the art urgently need to solve. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention discloses a low-permeability polytetrafluoroethylene tube and a preparation method thereof. The present invention prepares a low-permeability, high-performance polytetrafluoroethylene tube by adopting a pre-sintering and hot isostatic pressing process.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A low-permeability polytetrafluoroethylene tube is made of the following raw materials in parts by weight: 90-95 parts of TFE / HFP copolymer (i.e., modified polytetrafluoroethylene copolymerized by tetrafluoroethylene and hexafluoropropylene), 2-5 parts of auxiliary agent, 1-3 parts of nucleating agent, 0.5-1 part of antioxidant, and 0.1-1 part of antistatic agent.

[0008] Preferably, the TFE / HFP copolymer comprises 94 parts, an auxiliary agent comprises 3 parts, a nucleating agent comprises 2 parts, an antioxidant comprises 0.5 parts, and an antistatic agent comprises 0.5 parts.

[0009] Preferably, the auxiliary agent is one of paraffin oil, zinc stearate, and silicone oil; the nucleating agent is one of triphenyl phosphite, talc, silicon dioxide, and calcium carbonate; the antioxidant is a hindered phenol antioxidant or a phosphite antioxidant; the antistatic agent is one of dioctadecyl dimethyl ammonium chloride, hexadecyl trimethyl ammonium chloride, and octadecyl trimethyl ammonium chloride.

[0010] The present invention also discloses a method for preparing the TFE / HFP copolymer, and the specific steps are as follows:

[0011] S1. Prepare raw materials: weigh TFE (tetrafluoroethylene), HFP (hexafluoropropylene) and BPO (benzoyl peroxide) according to the mass ratio;

[0012] S2. Mixing raw materials: The TFE and HFP weighed in step S1 were added to a high-speed mixer, mixed at a speed of 1000 rpm for 5 to 8 min, and then BPO was added, and stirring was continued for 5 to 6 min to obtain a uniformly mixed mixture;

[0013] S3. Polymerization reaction: adding the mixed material in step S2 into a high-pressure reactor, placing the high-pressure reactor in a heating furnace to increase temperature and pressure, reacting for 4 to 6 hours at a temperature of 80 to 100° C. and a pressure of 20 to 40 MPa, and taking a sample once every hour during the reaction, monitoring the conversion rate by GPC (gel permeation chromatography) or NMR (nuclear magnetic resonance), and stopping heating and pressurizing when the conversion rate reaches 85 to 95%, cooling naturally to room temperature, releasing the pressure in the autoclave, and opening the autoclave to take out the reaction product;

[0014] S4 cooling and drying: The reaction product in step S3 was naturally cooled to room temperature, and the cooled product was placed in a vacuum drying oven at 60 to 70 ° C and dried for 24h to obtain a dry copolymer;

[0015] S5. Granulation: The dried copolymer in step S4 is added to a twin-screw granulator, and granulation is performed under the conditions of a screw speed of 300 rpm, a heating section temperature of 300°C, and a cooling section temperature of 200°C to obtain a copolymer-modified polytetrafluoroethylene powder, namely: TFE / HFP copolymer.

[0016] Preferably, in step S1, the mass ratio of TFE to HFP is (90-95):(5-10); and the BPO is 0.2%-0.8% of the total mass of TFE and HFP.

[0017] Preferably, in step S1, the mass ratio of TFE to HFP is 95:5, and the BPO is 0.5% of the total mass of TFE and HFP.

[0018] Preferably, in step S5, the particle size of the polytetrafluoroethylene powder is 0.3-0.4 mm.

[0019] The present invention also discloses a method for preparing the low-permeability polytetrafluoroethylene tube, comprising the following steps:

[0020] (1) Weigh TFE / HFP copolymer, auxiliary agent and nucleating agent, antioxidant and antistatic agent respectively according to weight parts for use;

[0021] (2) placing the TFE / HFP copolymer, additive, nucleating agent, antioxidant and antistatic agent in step (1) in a high-speed mixer and mixing them evenly, and then storing them at 10-15° C. for at least 24 hours;

[0022] (3) placing the mixture after being stored for a period of time in step (2) in a preforming machine, and pressing and molding at a pressure of 5 to 8 MPa and a compression rate of 40 to 50 mm / min to obtain a blank;

[0023] (4) placing the blank in step (3) on an extruder, and extruding at a cavity temperature of 40 to 50° C., a die temperature of 50 to 60° C., and an extrusion rate of 80 to 100 mm / min to obtain a green tube blank;

[0024] (5) After the green tube in step (4) is dried and pre-sintered, the green tube is subjected to hot isostatic pressing, that is, a low permeability polytetrafluoroethylene tube is obtained.

[0025] Preferably, in step (5), the drying temperature is 80-150°C and the time is 20-24 hours; the pre-sintering temperature is 200-300°C and the sintering time is 1.5-2.5 hours; the hot isostatic pressing pressure is 60-80 MPa, the temperature is 350-400°C and the time is 1-2 hours.

[0026] Preferably, in step (5), the drying temperature is 120°C and the time is 22 hours; the pre-sintering temperature is 250°C and the sintering time is 2 hours; the hot isostatic pressing pressure is 70 MPa, the temperature is 380°C and the time is 1.5 hours.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The present invention introduces the process of pre-sintering and hot isostatic pressing in the process of preparing the polytetrafluoroethylene tube, and the specific analysis is as follows:

[0029] (i) The pre-sintering disclosed in the present invention is carried out at a temperature of 200 to 300°C, which is lower than the melting point of the TFE / HFP copolymer (usually around 327°C) but much higher than its glass transition temperature Tg (about -80 to -100°C). This can promote the rearrangement of the molecular chains in the material and promote the initial crystallization of the material, but will not cause the material to completely melt to form a preliminary crystalline structure. The preliminary crystallization can improve the crystallinity of the material, provide more crystal nuclei for subsequent high-temperature sintering, and promote more uniform crystallization, thereby reducing defects and pores inside the material and improving the uniformity and density of the material. In addition, the pre-sintering disclosed in the present invention is carried out at a relatively low temperature, which can gradually release the stress inside the material, avoiding the occurrence of cracks or deformation caused by the large internal stress of the material during high-temperature sintering. At the same time, pre-sintering can reduce thermal shock during high-temperature sintering and improve the thermal stability of the material.

[0030] (ii) The temperature of the hot isostatic pressing treatment disclosed in the present invention is 330-400°C. Within this temperature range, the material after the above pre-sintering can be further crystallized to form a denser structure; at the same time, the applied pressure is 60-80MPa, which can force the pores in the material to close and improve the density of the material.

[0031] In summary, the present invention introduces pre-sintering and hot isostatic pressing processes. Pre-sintering is carried out at a temperature of 200-300°C, which can promote initial crystallization, gradually release internal stress, and reduce cracks and deformation during high-temperature sintering; hot isostatic pressing is carried out at a pressure of 60-80MPa and a temperature of 330-400°C, which can significantly reduce porosity and improve the microstructure of the material. Figure 1 As shown in (A), the polytetrafluoroethylene tube prepared by the process provided by the present invention has good fusion between resin particles, good density, good uniformity and consistency of the material; and the polytetrafluoroethylene tube prepared by the preparation method of the present invention has good mechanical properties and low permeability (as shown in Table 4), and its tensile pore index can reach 0.12%, and the permeability is low; at the same time, its fatigue resistance (as shown in Table 1 and Figure 2 ), after the pulse test, there are almost no longitudinal cracks at the buckling point and the tube body has no leakage, and the fatigue resistance is good; the compressive strength (as shown in Table 2) can reach 48MPa, which is 26.3% higher than that of the traditional preparation process (Comparative Example 1); the bending strength (as shown in Table 3), the change rate of the inner diameter after the bending test is only 4%, which is 9.5% lower than that of the traditional preparation process (Comparative Example 1); it can be seen that the present invention improves the density of the material and the anti-permeability of the material while ensuring other mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1The electron microscope images of Example 1 and Comparative Examples 1-4 of the present invention are shown;

[0033] Figure 2 The anatomical diagrams of each group of samples after the pulse test of Example 1 of the present invention and Comparative Examples 1-4 are shown. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The experimental methods in the following embodiments are all conventional methods unless otherwise specified; the experimental materials used are all commercially available unless otherwise specified.

[0035] The invention discloses a low-permeability polytetrafluoroethylene tube, which is made of the following raw materials in parts by weight: 90-95 parts of TFE / HFP copolymer, 2-5 parts of auxiliary agent, 1-3 parts of nucleating agent, 0.5-1 part of antioxidant, and 0.1-1 part of antistatic agent; the most preferred raw materials are 94 parts of TFE / HFP copolymer, 3 parts of auxiliary agent, 2 parts of nucleating agent, 0.5 part of antioxidant, and 0.5 part of antistatic agent.

[0036] The above-mentioned auxiliary agent is one of paraffin oil, zinc stearate, and silicone oil, the nucleating agent is one of triphenyl phosphite, talc, silicon dioxide, and calcium carbonate, the antioxidant is a hindered phenol antioxidant or a phosphite antioxidant, and the antistatic agent is one of dioctadecyl dimethyl ammonium chloride, hexadecyl trimethyl ammonium chloride, and octadecyl trimethyl ammonium chloride.

[0037] The preparation method of the above-mentioned TFE / HFP copolymer is as follows:

[0038] S1. Prepare raw materials: Weigh TFE, HFP and BPO respectively according to the mass ratio, wherein the mass ratio of TFE to HFP is (90-95):(5-10), and BPO is 0.2%-0.8% of the total mass of TFE and HFP; the most preferred mass ratio of TFE to HFP is 95:5, and BPO is 0.5% of the total mass of TFE and HFP.

[0039] S2. Mixing raw materials: Add the TFE and HFP weighed in step S1 into a high-speed mixer, mix at a speed of 1000 rpm for 5 to 8 minutes, then add BPO, and continue stirring and mixing for 5 to 6 minutes to obtain a uniformly mixed mixture.

[0040] S3. Polymerization reaction: Add the mixed material in step S2 into a high-pressure reactor, place the high-pressure reactor in a heating furnace to increase temperature and pressurize, react at a temperature of 80-100° C. and a pressure of 20-40 MPa for 4-6 hours, and take a sample once every hour during the reaction process, monitor the conversion rate by GPC or NMR, and when the conversion rate reaches 85-95%, stop heating and pressurizing, cool naturally to room temperature, release the pressure in the autoclave, open the autoclave and take out the reaction product.

[0041] S4. Cooling and drying: The reaction product in step S3 is naturally cooled to room temperature, and then the cooled product is placed in a vacuum drying oven and dried at 60-70° C. for 24 hours to obtain a dry copolymer.

[0042] S5. Granulation: Add the dried copolymer in step S4 into a twin-screw granulator and perform granulation at a screw speed of 300 rpm, a heating section temperature of 300°C, and a cooling section temperature of 200°C to obtain a copolymer-modified polytetrafluoroethylene powder, i.e., a TFE / HFP copolymer. The particle size of the obtained polytetrafluoroethylene powder is 0.3 to 0.4 mm.

[0043] The method for preparing a low permeability polytetrafluoroethylene tube using the above raw materials comprises the following specific steps:

[0044] (1) Weigh TFE / HFP copolymer, auxiliary agent and nucleating agent, antioxidant and antistatic agent respectively according to their weight parts and set aside.

[0045] (2) The TFE / HFP copolymer, additive, nucleating agent, antioxidant and antistatic agent in step (1) are placed in a high-speed mixer and mixed evenly, and then stored at 10-15° C. for at least 24 hours.

[0046] (3) placing the mixture stored for a period of time in step (2) in a preforming machine, and pressing and molding the mixture at a pressure of 5 to 8 MPa and a compression rate of 40 to 50 mm / min to obtain a blank.

[0047] (4) The blank in step (3) is placed on an extruder, and extruded at a cavity temperature of 40 to 50° C., a die temperature of 50 to 60° C., and an extrusion rate of 80 to 100 mm / min to obtain a green tube blank.

[0048] (5) The green tube blank in step (4) is placed in a drying oven and dried at 80-150° C. for 20-24 hours, and then placed in a sintering furnace and sintered at 200-300° C. for 1.5-2.5 hours for pre-sintering; after the pre-sintering is completed, after ensuring that the green tube blank has no cracks, bubbles or other defects, the surface of the tube is cleaned with a dust-free cloth and alcohol, and the tube is wrapped and sealed with a high-temperature resistant elastic rubber sleeve, and then the packaged tube is placed in the chamber of a hot isostatic pressing equipment, and hot isostatic pressing is performed at a pressure of 60-80 MPa, a temperature of 350-400° C., and a time of 1-2 hours. After the pre-sintering is completed, the pressure is slowly released and the tube is taken out, that is, a low permeability polytetrafluoroethylene tube is obtained.

[0049] The technical solution of the present invention is further described below in conjunction with specific embodiments and drawings:

[0050] Example 1

[0051] The preparation method of TFE / HFP copolymer in this embodiment comprises the following specific steps:

[0052] S1. Prepare raw materials: Use an electronic balance to weigh TFE and HFP according to the mass ratio (TFE:HFP=95:5); then weigh BPO so that BPO is 0.5% of the total mass of TFE and HFP.

[0053] S2. Mixing raw materials: Add the TFE and HFP weighed in step S1 into a high-speed mixer, mix at a speed of 1000 rpm for 6 minutes, then add BPO, and continue stirring and mixing for 5 minutes to obtain a uniformly mixed mixture.

[0054] S3. Polymerization reaction: Add the mixed material in step S2 into a high-pressure reactor, place the high-pressure reactor in a heating furnace to increase temperature and pressurize, react at a temperature of 90°C and a pressure of 30 MPa for 5 hours, and take samples once every hour during the reaction process, monitor the conversion rate by GPC, and when the conversion rate reaches 95%, stop heating and pressurizing, cool naturally to room temperature, release the pressure in the autoclave, open the autoclave and take out the reaction product.

[0055] S4. Cooling and drying: The reaction product in step S3 is naturally cooled to room temperature, and then the cooled product is placed in a vacuum drying oven and dried at 70° C. for 24 hours to obtain a dry copolymer.

[0056] S5. Granulation: Add the dried copolymer in step S4 into a twin-screw granulator and perform granulation at a screw speed of 300 rpm, a heating section temperature of 300°C, and a cooling section temperature of 200°C to obtain a copolymer-modified polytetrafluoroethylene powder, i.e., a TFE / HFP copolymer. The particle size of the obtained polytetrafluoroethylene powder is 0.3 to 0.4 mm.

[0057] The specific steps of preparing a low permeability polytetrafluoroethylene tube using the TFE / HFP copolymer prepared in the above embodiment as a raw material are as follows:

[0058] (1) Weigh out 94 parts of TFE / HFP copolymer, 3 parts of zinc stearate, 2 parts of triphenyl phosphite, 0.5 parts of hindered phenol antioxidant (Irganox 1010) and 0.5 parts of dioctadecyl dimethyl ammonium chloride respectively by weight and set aside.

[0059] (2) The weighed raw materials in step (1) are placed in a high-speed mixer and mixed evenly, and then stored at 12° C. for 30 h.

[0060] (3) The mixture stored for a period of time in step (2) is placed in a preforming machine, and is pressed and formed at a pressure of 6 MPa and a compression rate of 45 mm / min to obtain a blank.

[0061] (4) The blank in step (3) is placed on an extruder, and extruded at a cavity temperature of 45° C., a die temperature of 55° C., and an extrusion rate of 85 mm / min to obtain a raw tube blank.

[0062] (5) The green tube blank in step (4) is placed in a drying oven and dried at 120° C. for 22 hours, and then placed in a sintering furnace and sintered at 250° C. for 2 hours for pre-sintering; after the pre-sintering is completed, after ensuring that the green tube blank has no cracks, bubbles or other defects, the surface of the tube is cleaned with a dust-free cloth and alcohol, and the tube is wrapped and sealed with a high-temperature resistant elastic rubber sleeve, and then the packaged tube is placed in the chamber of a hot isostatic pressing equipment, and hot isostatic pressing is performed at a pressure of 70 MPa, a temperature of 380° C., and a time of 1.5 hours. After the pre-sintering is completed, the pressure is slowly released and the tube is taken out, that is, a low permeability polytetrafluoroethylene tube is obtained.

[0063] Example 2

[0064] The preparation method of TFE / HFP copolymer in this embodiment comprises the following specific steps:

[0065] S1. Prepare raw materials: Use an electronic balance to weigh TFE and HFP according to the mass ratio (TFE:HFP=95:10); then weigh BPO so that BPO is 0.2% of the total mass of TFE and HFP.

[0066] S2. Mixing raw materials: Add the TFE and HFP weighed in step S1 into a high-speed mixer, mix at a speed of 1000 rpm for 8 minutes, then add BPO, and continue stirring and mixing for 6 minutes to obtain a uniformly mixed mixture.

[0067] S3. Polymerization reaction: Add the mixed material in step S2 into a high-pressure reactor, place the high-pressure reactor in a heating furnace to increase temperature and pressurize, react at a temperature of 100°C and a pressure of 20 MPa for 6 hours, and take samples once every hour during the reaction process, monitor the conversion rate by GPC, and when the conversion rate reaches 85%, stop heating and pressurizing, cool naturally to room temperature, release the pressure in the autoclave, open the autoclave and take out the reaction product.

[0068] S4. Cooling and drying: The reaction product in step S3 is naturally cooled to room temperature, and then the cooled product is placed in a vacuum drying oven and dried at 60° C. for 24 h to obtain a dry copolymer.

[0069] S5. Granulation: Add the dried copolymer in step S4 into a twin-screw granulator and perform granulation at a screw speed of 300 rpm, a heating section temperature of 300°C, and a cooling section temperature of 200°C to obtain a copolymer-modified polytetrafluoroethylene powder, i.e., a TFE / HFP copolymer. The particle size of the obtained polytetrafluoroethylene powder is 0.3 to 0.4 mm.

[0070] The specific steps of preparing a low permeability polytetrafluoroethylene tube using the TFE / HFP copolymer prepared in the above embodiment as a raw material are as follows:

[0071] (1) Weigh out 90 parts of TFE / HFP copolymer, 2 parts of paraffin oil, 1 part of silicon dioxide, 0.7 parts of hindered phenol antioxidant (Irganox 1010) and 0.7 parts of hexadecyltrimethylammonium chloride respectively by weight and set aside.

[0072] (2) The weighed raw materials in step (1) are placed in a high-speed mixer and mixed evenly, and then stored at 10° C. for 35 h.

[0073] (3) The mixture stored for a period of time in step (2) is placed in a preforming machine, and is pressed at a pressure of 5 MPa and a compression rate of 40 mm / min to obtain a blank.

[0074] (4) The blank in step (3) is placed on an extruder, and extruded at a cavity temperature of 40° C., a die temperature of 50° C., and an extrusion rate of 80 mm / min to obtain a green tube blank.

[0075] (5) The green tube blank in step (4) is placed in a drying oven and dried at 80° C. for 20 h, and then placed in a sintering furnace and sintered at 200° C. for 1.5 h for pre-sintering; after the pre-sintering is completed, after ensuring that the sintered green tube blank has no cracks, bubbles or other defects, the surface of the tube is cleaned with a dust-free cloth and alcohol, and the tube is wrapped and sealed with a high-temperature resistant elastic rubber sleeve, and then the packaged tube is placed in the chamber of a hot isostatic pressing equipment, and hot isostatic pressing treatment is performed at a pressure of 60 MPa, a temperature of 350° C., and a time of 1 hour. After the pre-sintering is completed, the pressure is slowly released and the tube is taken out, that is, a low permeability polytetrafluoroethylene tube is obtained.

[0076] Example 3

[0077] The preparation method of TFE / HFP copolymer in this embodiment comprises the following specific steps:

[0078] S1. Prepare raw materials: Use an electronic balance to weigh TFE and HFP according to the mass ratio (TFE:HFP=95:5); then weigh BPO according to the ratio of BPO to 0.8% of the total mass of TFE and HFP.

[0079] S2. Mixing raw materials: Add the TFE and HFP weighed in step S1 into a high-speed mixer, mix at a speed of 1000 rpm for 8 minutes, then add BPO, and continue stirring and mixing for 6 minutes to obtain a uniformly mixed mixture.

[0080] S3. Polymerization reaction: Add the mixed material in step S2 into a high-pressure reactor, place the high-pressure reactor in a heating furnace to increase temperature and pressurize, react at a temperature of 100°C and a pressure of 40MPa for 4 hours, and take samples once every hour during the reaction process, monitor the conversion rate by GPC, and when the conversion rate reaches 90%, stop heating and pressurizing, cool naturally to room temperature, release the pressure in the autoclave, open the autoclave and take out the reaction product.

[0081] S4. Cooling and drying: The reaction product in step S3 is naturally cooled to room temperature, and then the cooled product is placed in a vacuum drying oven and dried at 70° C. for 24 hours to obtain a dry copolymer.

[0082] S5. Granulation: Add the dried copolymer in step S4 into a twin-screw granulator and perform granulation at a screw speed of 300 rpm, a heating section temperature of 300°C, and a cooling section temperature of 200°C to obtain a copolymer-modified polytetrafluoroethylene powder, i.e., a TFE / HFP copolymer. The particle size of the obtained polytetrafluoroethylene powder is 0.3 to 0.4 mm.

[0083] The specific steps of preparing a low permeability polytetrafluoroethylene tube using the TFE / HFP copolymer prepared in the above embodiment as a raw material are as follows:

[0084] (1) Weigh out 95 parts of TFE / HFP copolymer, 5 parts of paraffin oil, 1 part of triphenyl phosphite, 1 part of phosphite antioxidant (Irgafos 168) and 0.1 part of octadecyltrimethylammonium chloride respectively by weight and set aside.

[0085] (2) The weighed raw materials in step (1) are placed in a high-speed mixer and mixed evenly, and then stored at 15° C. for 24 hours.

[0086] (3) The mixture stored for a period of time in step (2) is placed in a preforming machine, and is pressed and formed at a pressure of 8 MPa and a compression rate of 50 mm / min to obtain a blank.

[0087] (4) The blank in step (3) is placed on an extruder, and extruded at a cavity temperature of 50° C., a die temperature of 60° C., and an extrusion rate of 100 mm / min to obtain a green tube blank.

[0088] (5) The green tube blank in step (4) is placed in a drying oven and dried at 150° C. for 24 hours, and then placed in a sintering furnace and sintered at 300° C. for 2.5 hours for pre-sintering; after the pre-sintering is completed, after ensuring that the sintered green tube blank has no cracks, bubbles or other defects, the surface of the tube is cleaned with a dust-free cloth and alcohol, and the tube is wrapped and sealed with a high-temperature resistant elastic rubber sleeve, and then the packaged tube is placed in the chamber of a hot isostatic pressing equipment, and hot isostatic pressing is performed at a pressure of 80 MPa, a temperature of 380° C., and a time of 2 hours. After the pre-sintering is completed, the pressure is slowly released and the tube is taken out, that is, a low permeability polytetrafluoroethylene tube is obtained.

[0089] Example 4

[0090] The preparation method of TFE / HFP copolymer in this embodiment comprises the following specific steps:

[0091] S1. Prepare raw materials: Use an electronic balance to weigh TFE and HFP according to the mass ratio (TFE:HFP=90:10); then weigh BPO according to the ratio of BPO to 0.6% of the total mass of TFE and HFP.

[0092] S2. Mixing raw materials: Add the TFE and HFP weighed in step S1 into a high-speed mixer, mix at a speed of 1000 rpm for 8 minutes, then add BPO, and continue stirring and mixing for 6 minutes to obtain a uniformly mixed mixture.

[0093] S3. Polymerization reaction: Add the mixed material in step S2 into a high-pressure reactor, place the high-pressure reactor in a heating furnace to increase temperature and pressurize, react at a temperature of 90°C and a pressure of 30 MPa for 5 hours, and take samples once every hour during the reaction process, monitor the conversion rate by GPC, and when the conversion rate reaches 90%, stop heating and pressurizing, cool naturally to room temperature, release the pressure in the autoclave, open the autoclave and take out the reaction product.

[0094] S4. Cooling and drying: The reaction product in step S3 is naturally cooled to room temperature, and then the cooled product is placed in a vacuum drying oven and dried at 70° C. for 24 hours to obtain a dry copolymer.

[0095] S5. Granulation: Add the dried copolymer in step S4 into a twin-screw granulator and perform granulation at a screw speed of 300 rpm, a heating section temperature of 300°C, and a cooling section temperature of 200°C to obtain a copolymer-modified polytetrafluoroethylene powder, i.e., a TFE / HFP copolymer. The particle size of the obtained polytetrafluoroethylene powder is 0.3 to 0.4 mm.

[0096] The specific steps of preparing a low permeability polytetrafluoroethylene tube using the TFE / HFP copolymer prepared in the above embodiment as a raw material are as follows:

[0097] (1) Weigh out 92 parts of TFE / HFP copolymer, 3 parts of zinc stearate, 1.5 parts of triphenyl phosphite, 0.8 parts of phosphite antioxidant (Irgafos 168) and 0.5 parts of octadecyltrimethylammonium chloride respectively by weight and set aside.

[0098] (2) The weighed raw materials in step (1) are placed in a high-speed mixer and mixed evenly, and then stored at 15° C. for 30 h.

[0099] (3) The mixture stored for a period of time in step (2) is placed in a preforming machine, and is pressed and formed at a pressure of 6 MPa and a compression rate of 45 mm / min to obtain a blank.

[0100] (4) The blank in step (3) is placed on an extruder, and extruded at a cavity temperature of 45° C., a die temperature of 55° C., and an extrusion rate of 90 mm / min to obtain a green tube blank.

[0101] (5) The green tube blank in step (4) is placed in a drying oven and dried at 80° C. for 24 h, and then placed in a sintering furnace and sintered at 200° C. for 2.5 h for pre-sintering; after the pre-sintering is completed, after ensuring that the sintered green tube blank has no cracks, bubbles or other defects, the surface of the tube is cleaned with a dust-free cloth and alcohol, and the tube is wrapped and sealed with a high-temperature resistant elastic rubber sleeve, and then the packaged tube is placed in the chamber of a hot isostatic pressing equipment, and hot isostatic pressing is performed at a pressure of 60 MPa, a temperature of 400° C., and a time of 2 hours. After the pre-sintering is completed, the pressure is slowly released and the tube is taken out, that is, a low permeability polytetrafluoroethylene tube is obtained.

[0102] Comparative Example 1

[0103] The raw materials and formula of this comparative example are the same as those of Example 1, except that hot isostatic pressing is not used in the preparation process.

[0104] The preparation method of the polytetrafluoroethylene tube in this comparative example comprises the following specific steps:

[0105] (1) Weigh out 94 parts of TFE / HFP copolymer, 3 parts of zinc stearate, 2 parts of triphenyl phosphite, 0.5 parts of hindered phenol antioxidant (Irganox 1010) and 0.5 parts of dioctadecyl dimethyl ammonium chloride respectively by weight and set aside.

[0106] (2) The weighed raw materials in step (1) are placed in a high-speed mixer and mixed evenly, and then stored at 12° C. for 30 h.

[0107] (3) The mixture stored for a period of time in step (2) is placed in a preforming machine, and is pressed and formed at a pressure of 6 MPa and a compression rate of 45 mm / min to obtain a blank.

[0108] (4) The blank in step (3) is placed on an extruder, and extruded at a cavity temperature of 45° C., a die temperature of 55° C., and an extrusion rate of 85 mm / min to obtain a raw tube blank.

[0109] (5) The green tube blank in step (4) is placed in a drying oven and dried at 120° C. for 22 hours, and then placed in a sintering furnace and sintered at 250° C. for 2 hours, and then the temperature is raised to 380° C. and sintered for 1.5 hours to obtain a polytetrafluoroethylene tube.

[0110] Comparative Example 2

[0111] The raw materials and formula of this comparative example are the same as those of Example 1, except that the pre-sintering process is not used in the preparation process.

[0112] The preparation method of the polytetrafluoroethylene tube in this comparative example comprises the following specific steps:

[0113] (1) Weigh out 94 parts of TFE / HFP copolymer, 3 parts of zinc stearate, 2 parts of triphenyl phosphite, 0.5 parts of hindered phenol antioxidant (Irganox 1010) and 0.5 parts of dioctadecyl dimethyl ammonium chloride respectively by weight and set aside.

[0114] (2) The weighed raw materials in step (1) are placed in a high-speed mixer and mixed evenly, and then stored at 12° C. for 30 h.

[0115] (3) The mixture stored for a period of time in step (2) is placed in a preforming machine, and is pressed and formed at a pressure of 6 MPa and a compression rate of 45 mm / min to obtain a blank.

[0116] (4) The blank in step (3) is placed on an extruder, and extruded at a cavity temperature of 45° C., a die temperature of 55° C., and an extrusion rate of 85 mm / min to obtain a raw tube blank.

[0117] (5) The green tube in step (4) is placed in a drying oven at 120° C. and dried for 22 h. After ensuring that the green tube has no cracks, bubbles or other defects, the surface of the tube is cleaned with a dust-free cloth and alcohol, and the tube is wrapped and sealed with a high-temperature resistant elastic rubber sleeve. The packaged tube is then placed in a chamber of a hot isostatic pressing device and hot isostatically pressed at a pressure of 70 MPa, a temperature of 380° C., and a time of 1.5 hours. After the hot isostatic pressing treatment is completed, the pressure is slowly released and the tube is taken out, thereby obtaining a low permeability polytetrafluoroethylene tube.

[0118] Comparative Example 3

[0119] The raw materials and formula of this comparative example are the same as those of Example 1, except that pre-sintering and hot isostatic pressing are not used in the preparation process.

[0120] (1) Weigh out 94 parts of TFE / HFP copolymer, 3 parts of zinc stearate, 2 parts of triphenyl phosphite, 0.5 parts of hindered phenol antioxidant (Irganox 1010) and 0.5 parts of dioctadecyl dimethyl ammonium chloride respectively by weight and set aside.

[0121] (2) The weighed raw materials in step (1) are placed in a high-speed mixer and mixed evenly, and then stored at 12° C. for 30 h.

[0122] (3) The mixture stored for a period of time in step (2) is placed in a preforming machine, and is pressed and formed at a pressure of 6 MPa and a compression rate of 45 mm / min to obtain a blank.

[0123] (4) The blank in step (3) is placed on an extruder, and extruded at a cavity temperature of 45° C., a die temperature of 55° C., and an extrusion rate of 85 mm / min to obtain a raw tube blank.

[0124] (5) The green tube blank in step (4) is placed in a drying oven at 120° C. and dried for 22 hours, and then placed in a sintering furnace and heated to 380° C. and sintered for 3.5 hours to obtain a polytetrafluoroethylene tube.

[0125] Comparative Example 4

[0126] The difference between this comparative example and Example 1 is that polytetrafluoroethylene dispersion is used, and the other raw materials, formula and preparation process are exactly the same.

[0127] The preparation method of the polytetrafluoroethylene tube in this comparative example comprises the following specific steps:

[0128] (1) Weigh out 94 parts of T polytetrafluoroethylene dispersion, 3 parts of zinc stearate, 2 parts of triphenyl phosphite, 0.5 parts of hindered phenol antioxidant (Irganox 1010) and 0.5 parts of dioctadecyl dimethyl ammonium chloride respectively by weight for later use.

[0129] (2) The weighed raw materials in step (1) are placed in a high-speed mixer and mixed evenly, and then stored at 12° C. for 30 h.

[0130] (3) The mixture stored for a period of time in step (2) is placed in a preforming machine, and is pressed and formed at a pressure of 6 MPa and a compression rate of 45 mm / min to obtain a blank.

[0131] (4) The blank in step (3) is placed on an extruder, and extruded at a cavity temperature of 45° C., a die temperature of 55° C., and an extrusion rate of 85 mm / min to obtain a raw tube blank.

[0132] (5) The green tube blank in step (4) is placed in a drying oven and dried at 120° C. for 22 hours, and then placed in a sintering furnace and sintered at 250° C. for 2 hours for pre-sintering; after the pre-sintering is completed, after ensuring that the green tube blank has no cracks, bubbles or other defects, the surface of the tube is cleaned with a dust-free cloth and alcohol, and the tube is wrapped and sealed with a high-temperature resistant elastic rubber sleeve, and then the packaged tube is placed in the chamber of a hot isostatic pressing equipment, and hot isostatic pressing is performed at a pressure of 70 MPa, a temperature of 380° C., and a time of 1.5 hours. After the pre-sintering is completed, the pressure is slowly released and the tube is taken out, that is, a polytetrafluoroethylene tube is obtained.

[0133] Performance test results:

[0134] The performance of the polytetrafluoroethylene tubes prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 was tested as follows.

[0135] 1. Electron microscope image analysis:

[0136] The electron microscope images of the polytetrafluoroethylene tubes of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 5 under a 1000x lens are as follows: Figure 1 As shown (A: Example 1, B: Comparative Example 1, C: Comparative Example 2, D: Comparative Example 3, E: Comparative Example 4), it can be seen from the figure: Figure 1 The boundaries between the resin particles in (A) are difficult to distinguish, and the pores between the particles are few and small, indicating that the resin particles are well fused together, with good density, and the uniformity and consistency of the material are good; Figure 1 In (B), most of the resin particles are fused together, the boundaries between particles are blurred, but the pores between particles are relatively small. Figure 1 The large number in (A) indicates Figure 1 (B) The uniformity and consistency of the material are better Figure 1 (A) Slightly worse; Figure 1 In (C), a small number of resin particles are well fused, but most of the resin particles are not well fused. The boundaries between particles are relatively clear, and the pores between particles are smaller than those in (B), indicating that the crystallinity between resin particles is relatively high. Figure 1 (A) and Figure 1 (B) The material is poor; Figure 1 (D) Most of the resin particles are not well fused, only a few of them are fused together, and the boundaries between the resin particles are relatively clear, and the pores between the particles are numerous and large; Figure 1 (E) The fusion between the resin particles is relatively good Figure 1 (A) Poor, the number of pores between particles is large but the pore size is small. This shows that: pre-sintering at a lower temperature can promote the initial crystallization of the material, improve the crystallinity of the material, provide more crystal nuclei for subsequent high-temperature sintering, promote more uniform crystallization, and reduce defects and pores inside the material; hot isostatic pressing under high pressure and high temperature can further promote uniform crystallization of the material, reduce grain boundary defects, and force the pores in the material to close, improve the density of the material, and further improve the uniformity and consistency of the material; at the same time, the copolymer-modified polytetrafluoroethylene has a low melt viscosity and good fluidity compared to the unmodified polytetrafluoroethylene, which can promote better crystallization and densification.

[0137] 2. Pulse test:

[0138] The polytetrafluoroethylene tubes prepared in the above five embodiments (Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4) were subjected to pulse tests according to the AS standard requirements, with the number of pulses being 600,000 times, the working pressure being 20 MPa, and the pulse frequency being 80 times / minute. Three sample tubes were taken from each embodiment for testing, and the test results are shown in Table 1 below.

[0139] Table 1

[0140]

[0141] The samples from each group after the above test were dissected, and the pictures of each group after dissection are as follows Figure 2 As shown (A: Example 1, B: Comparative Example 1, C: Comparative Example 2, D: Comparative Example 3, E: Comparative Example 4). It can be seen from the figure: Figure 2 (A) After the medium pulse test, there are almost no wrinkles at the buckle position; Figure 2 (B) Figure 2 (C) Figure 2 (D) and Figure 2 (E) After the pulse test, multiple longitudinal wrinkles appeared at the buckling point. Figure 2 (E) There are fewer wrinkles. Figure 2 (D) There are the most wrinkles and they are piled up and overlapped together; this shows that the fatigue resistance of the polytetrafluoroethylene tube prepared by the preparation process of the present invention is significantly better than that of the polytetrafluoroethylene tube prepared by the conventional process.

[0142] 3. Compression test:

[0143] The polytetrafluoroethylene tubes prepared in the above five embodiments (Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4) were tested for pressure resistance by taking samples of the same size. The samples were then placed on a pressure resistance machine for a pressure resistance test. The test results are shown in Table 2 below.

[0144] Table 2

[0145]

[0146] As can be seen from Table 2, the polytetrafluoroethylene tube prepared in Example 1 of the present invention is significantly better than the polytetrafluoroethylene tubes prepared in Comparative Examples 1-4. This is because the present invention introduces pre-sintering and hot isostatic pressing processes, and the pre-sintering is carried out at a temperature of 200-300°C, which is lower than the melting point of the TFE / HFP copolymer (usually around 327°C), but much higher than its glass transition temperature Tg (about -80--100°C), which can promote the rearrangement of the molecular chains in the material, promote the initial crystallization of the material, provide more crystal nuclei for subsequent high-temperature sintering, and promote more uniform crystallization. The uniform crystal structure can effectively disperse the external pressure, avoid local stress concentration, and further improve the compressive performance of the material; at the same time, the hot isostatic pressing treatment is carried out under high pressure and high temperature, which can force the pores in the material to close, further improve the density of the material, and significantly improve the mechanical properties of the material, especially the compressive strength.

[0147] 4. Bending detection:

[0148] The polytetrafluoroethylene tubes prepared in the above five embodiments (Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4) were tested by taking samples of the same size, and installed on a bending test equipment according to the bending radius required by the AS standard, and a bending test was performed. Table 3 shows the changes in the inner diameters of the samples before and after bending, and the rate of change of the inner diameter = (inner diameter after bending - inner diameter before bending) / inner diameter before bending.

[0149] Table 3

[0150]

[0151] It can be seen from Table 3 that the change rate of the inner diameter after the bending test in Example 1 of the present invention is only 4%, and the change rates of the inner diameters of Comparative Examples 1-4 before and after bending are all more than 15%; in particular, although the formula of Comparative Example 3 is the same as that of Example 1 of the present invention, the preparation process is different, and the change rate of the inner diameter before and after bending even reaches 20%; although Comparative Example 4 does not use the same copolymer-modified polytetrafluoroethylene as Example 1 of the present invention, it uses the same preparation process, and the change rate of the inner diameter before and after bending is 17.92%, which is greater than that of Example 1, but less than that of other comparative examples; this shows that the polytetrafluoroethylene tube prepared by the present invention also has good bending strength.

[0152] 5. Tensile pore index:

[0153] The tensile porosity index is mainly used to measure the change in specific gravity of the sample before and after stretching. Usually, the prepared polytetrafluoroethylene tube is stretched to 200% of its original length within 1 to 1.5 minutes, and then the specific gravity of the sample before and after stretching is measured. The larger the tensile porosity index value, the more pores in the material, the higher the permeability, and the worse the material's resistance to stress cracking. (The volume can be calculated using the displacement method). Three sample tubes were taken from each embodiment for testing. The test results are shown in Table 4 below.

[0154] Table 4

[0155]

[0156] It can be seen from Table 4 that the tensile porosity index in Example 1 of the present invention is only between 0.12% and 0.17%, indicating that the material has fewer pores, better density and uniformity, and lower permeability; the comparative example 3 even reaches more than 1%, indicating that the prepared tube material has more internal pores, poor density, and higher permeability.

[0157] In summary, the above test results show that the fatigue resistance, compressive strength, bending strength and other mechanical properties of the polytetrafluoroethylene tube prepared in Example 1 of the present invention are better than those of the polytetrafluoroethylene tubes prepared in Comparative Examples 1-4, and the tensile pore index of Example 1 of the present invention is also lower, that is, the pores inside the material are less, the uniformity and density of the material are better, and the anti-permeability is relatively excellent. This shows that the polytetrafluoroethylene tube prepared by the formula and preparation process disclosed in the present invention improves the anti-permeability of the material while ensuring other mechanical properties, that is, it has lower permeability.

[0158] The above is a detailed introduction to a low permeability polytetrafluoroethylene tube and a preparation method thereof disclosed in the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and core idea of ​​the present invention. It should be pointed out that for ordinary technicians in this technical field, the present invention can also be improved and modified without departing from the principle of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A low permeability polytetrafluoroethylene tube, characterized in that: The invention is prepared from the following raw materials in parts by weight: 90-95 parts of TFE / HFP copolymer, 2-5 parts of auxiliary agent, 1-3 parts of nucleating agent, 0.5-1 part of antioxidant and 0.1-1 part of antistatic agent.

2. A low permeability polytetrafluoroethylene tube according to claim 1, characterized in that: The TFE / HFP copolymer is 94 parts, the auxiliary agent is 3 parts, the nucleating agent is 2 parts, the antioxidant is 0.5 parts, and the antistatic agent is 0.5 parts.

3. A low permeability polytetrafluoroethylene tube according to claim 1, characterized in that: The auxiliary agent is one of paraffin oil, zinc stearate, and silicone oil; the nucleating agent is one of triphenyl phosphite, talcum powder, silicon dioxide, and calcium carbonate; the antioxidant is a hindered phenol antioxidant or a phosphite antioxidant; the antistatic agent is one of dioctadecyl dimethyl ammonium chloride, hexadecyl trimethyl ammonium chloride, and octadecyl trimethyl ammonium chloride.

4. A low permeability polytetrafluoroethylene tube according to claim 1, characterized in that: The preparation method of the TFE / HFP copolymer is as follows: S1. Prepare raw materials: weigh TFE, HFP and BPO respectively according to the mass ratio; S2. Mixing raw materials: The TFE and HFP weighed in step S1 were added to a high-speed mixer, mixed at a speed of 1000 rpm for 5 to 8 min, and then BPO was added, and stirring was continued for 5 to 6 min to obtain a uniformly mixed mixture; S3. Polymerization reaction: adding the mixture in step S2 to a high-pressure reactor, placing the high-pressure reactor in a heating furnace to increase temperature and pressure, reacting for 4 to 6 hours at a temperature of 80 to 100 ° C and a pressure of 20 to 40 MPa, and taking a sample once every hour during the reaction, monitoring the conversion rate by GPC or NMR, and when the conversion rate reaches 85 to 95%, stopping heating and pressurizing, cooling naturally to room temperature, releasing the pressure in the autoclave, opening the autoclave and taking out the reaction product; S4 cooling and drying: The reaction product in step S3 was naturally cooled to room temperature, and the cooled product was placed in a vacuum drying oven at 60 to 70 ° C and dried for 24h to obtain a dry copolymer; S5. Granulation: The dried copolymer in step S4 is added to a twin-screw granulator, and granulation is performed under the conditions of a screw speed of 300 rpm, a heating section temperature of 300°C, and a cooling section temperature of 200°C to obtain a copolymer-modified polytetrafluoroethylene powder, namely: TFE / HFP copolymer.

5. A low permeability polytetrafluoroethylene tube according to claim 4, characterized in that: In step S1, the mass ratio of TFE to HFP is (90-95):(5-10); and the BPO is 0.2%-0.8% of the total mass of TFE and HFP.

6. A low permeability polytetrafluoroethylene tube according to claim 5, characterized in that: In step S1, the mass ratio of TFE to HFP is 95:5, and the BPO is 0.5% of the total mass of TFE and HFP.

7. A low permeability polytetrafluoroethylene tube according to claim 4, characterized in that: In step S5, the particle size of the polytetrafluoroethylene powder is 0.3-0.4 mm.

8. The method for preparing a low permeability polytetrafluoroethylene tube according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh TFE / HFP copolymer, auxiliary agent and nucleating agent, antioxidant and antistatic agent respectively according to weight parts for use; (2) placing the TFE / HFP copolymer, additive, nucleating agent, antioxidant and antistatic agent in step (1) in a high-speed mixer and mixing them evenly, and then storing them at 10-15° C. for at least 24 hours; (3) placing the mixture after being stored for a period of time in step (2) in a preforming machine, and pressing and molding at a pressure of 5 to 8 MPa and a compression rate of 40 to 50 mm / min to obtain a blank; (4) placing the blank in step (3) on an extruder, and extruding at a cavity temperature of 40 to 50° C., a die temperature of 50 to 60° C., and an extrusion rate of 80 to 100 mm / min to obtain a green tube blank; (5) After drying and pre-sintering the green tube in step (4), the green tube is subjected to hot isostatic pressing, that is, a low permeability polytetrafluoroethylene tube is obtained.

9. The method for preparing a low permeability polytetrafluoroethylene tube according to claim 8, characterized in that: In step (5), the drying temperature is 80-150°C and the time is 20-24 hours; the pre-sintering temperature is 200-300°C and the sintering time is 1.5-2.5 hours; the hot isostatic pressing pressure is 60-80MPa, the temperature is 350-400°C and the time is 1-2 hours.

10. The method for preparing a low permeability polytetrafluoroethylene tube according to claim 9, characterized in that: In step (5), the drying temperature is 120°C and the time is 22 hours; the pre-sintering temperature is 250°C and the sintering time is 2 hours; the hot isostatic pressing pressure is 70 MPa, the temperature is 380°C and the time is 1.5 hours.